Production of ethanol from tapioca sugars - Farah Asilah, Binti Azri (Universiti Malaysia Sarawak, UNIMAS, 2012)
Tapioca (Manihot esculenta) is an excellent source of starch which can be hydrolyzed to produce reducing sugars utilizing bacterial enzymes and subsequently fermented to produce ethanol. The objectives of this study are to maximize the production of ethanol from hydrolyzed tapioca sugars (mainly glucose) and to study the effects of sugar concentrations on the productivity of ethanol. Enzymatic hydrolysis was carried out in 2 stages namely liquefaction and saccharification with the help of enzymes Termamyl SC and Dextroxyme under optimum conditions. Then, the tapioca sugar syrup was used in batch fermentation using Saccharomyces cerevisiae, a type of baker yeast obtained in the market. The glucose recovery resulted from tapioca flour was higher compared to fresh tapioca in a range of 63- 68% and 39-45%, respectively. Three different concentrations (50, 100 and 150 g/L) of tapioca sugar from tapioca flour and fresh tapioca were tested in shake-flask fermentation for 24 hours to observe the optimum sugar concentration to generate highest yield of ethanol. The ethanol obtained at 12 hours was 25.70 g/L from 50 g/L of TFS which represented 50.2% of ethanol yield compared to 47.59 g/L from 100 g/L glucose and 58.53 g/L from 150 g/L glucose with 48.0% and 38.3% of ethanol yield, respectively. Meanwhile, ethanol obtained at 12 hours from FTS was 25.89 g/L, 40.18 g/L and 50.19 g/L from 50 g/L, 100 g/L and 150 g/L of glucose which represented 51.1%, 40.8% and 33.3% of ethanol yield, respectively. Moreover, 150 g/L resulted a residual glucose at the end of 24 hours process for both types of sugar. Therefore, 50 g/L is selected as the best glucose concentration of ethanol fermentation for economical reason and to minimize the residual glucose.